Preparation and characterization of silicon dioxide nanoparticles and thin films - Lee, Shet Khiun (Universiti Malaysia Sarawak (UNIMAS), 2007)
Silicon dioxide colloidal suspensions synthesized by the microemulsion method had higher stability than that prepared by the sol-gel method. The higher stability of silicon dioxide colloidal suspension prepared by microemulsion method was evidenced by the effect of aging which was observable in the order of weeks as compared to hours for colloidal suspension prepared by the sol-gel method. Silicon dioxide colloidal suspensions prepared by the sol-gel method formed precipitate after one day of preparation. Fourier Transformed Infrared Spectrometer (FTIR) had confirmed the presence of silicon dioxide in the sol with characteristic absorption bands at 800-1260 cm-1. UV-visible spectra of silicon dioxide colloidal suspensions prepared by microemulsion method showed lower λmax than that of the sol-gel method, indicating the formation of aggregates or particles with relatively smaller sizes. Besides, silicon dioxide colloidal suspensions were observed to have lower λmax after being dialyzed against ultrapure water. The morphology and particle size distribution of silicon dioxide thin films were studied by the Scanning Electron Microscopy (SEM) which indicated the presence of nano-sized silicon dioxide particles.